An ultra-light high-plastic high-forming magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation and a preparation method thereof

CN122959591APending Publication Date: 2026-10-23QINGHAI SALT LAKE IND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610907251.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但常规镁锂合金在热加工过程中晶粒易快速粗化,组织均匀性差,晶界变形协调性不足,导致材料塑性偏低、成形性能不佳,难以满足深冲等复杂成形工艺需求,严重限制了其工程化应用

Benefits of technology

(1)通过调控Zn、Er晶界偏聚,有效稳定晶界、细化晶粒、均匀组织,显著提升镁锂合金变形协调性,实现高塑性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959591A_ABST
    Figure CN122959591A_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on Zn, Er grain boundary segregation ultra-light high plastic high forming magnesium-lithium alloy plate and preparation method thereof, belong to metal material technical field.Preparation steps are: take pure magnesium ingot, pure zinc ingot, magnesium-lithium intermediate alloy, magnesium-erbium intermediate alloy as raw material;Alloy melt is obtained by heating and melting raw material;Alloy melt is cast into alloy ingot;After alloy ingot preheating, extrusion forming is obtained magnesium-lithium alloy extrusion slab, and the target magnesium-lithium alloy plate is obtained by carrying out on-line heating rolling deformation treatment to extrusion slab.The density of the alloy plate is less than 1.55g / cm 3 , tensile strength 160~190MPa, yield strength 140~165MPa, elongation 15~45%, cupping value 8.5~13.0mm, while ensuring the characteristics of alloy ultra-light, significantly improve plasticity, and preparation process is simple, without special equipment, easy industrial production, can be widely used in electronic communication and other fields of lightweight structural components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal materials technology, and in particular to an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation and its preparation method. Background Technology

[0002] Magnesium-lithium alloys are currently the lightest metallic structural materials, possessing a low density (1.3-1.6 g / cm³). 3 With its outstanding advantages such as high specific strength, conventional magnesium-lithium alloys have shown great application potential in aerospace, weaponry, and 3C electronics. However, during hot working, conventional magnesium-lithium alloys are prone to rapid grain coarsening, poor microstructure uniformity, and insufficient grain boundary deformation coordination, resulting in low material plasticity and poor formability. This makes it difficult to meet the requirements of complex forming processes such as deep drawing, severely limiting their engineering applications.

[0003] To improve the above problems, the grain boundary control of magnesium-lithium alloys is currently attempted to pin the grain boundaries by adding a single element or a coarse second phase, but the following main limitations still exist: (1) the effect of single-element grain boundary control is limited; (2) the distribution of coarse second phase is difficult to control evenly, resulting in poor microstructure uniformity and insufficient deformation coordination, which in turn damages plasticity; (3) there is a lack of precise control of multi-element synergistic segregation; (4) the hot deformation process is disconnected from the segregation behavior.

[0004] Therefore, developing a preparation method that can precisely control the synergistic grain boundary segregation of multiple elements through hot deformation process, thereby simultaneously improving the plasticity and formability of magnesium-lithium alloys, is of great value. Summary of the Invention

[0005] The purpose of this invention is to provide an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation and its preparation method. By designing a targeted extrusion-online rolling composite process, the synergistic segregation behavior of Zn and Er elements at the grain boundaries is precisely controlled. The synergistic solute dragging effect is used to stabilize the grain boundaries, refine the microstructure, and improve deformation coordination, thereby obtaining an ultralight magnesium-lithium alloy sheet with high plasticity and excellent formability.

[0006] To achieve the above objectives, the present invention provides an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation. The magnesium-lithium alloy sheet is composed of the following components by mass percentage: Li 5.0-15.0 wt.%, Zn 1.0-4.0 wt.%, Er 0.5-5.0 wt.%, with the balance being Mg and unavoidable impurities, wherein the total impurity content is ≤0.3 wt.%.

[0007] Preferably, the magnesium-lithium alloy plate is composed of the following components by mass percentage: Li 8.0-12.0 wt.%, Zn 2.5-3.5 wt.%, Er 1.5-3.0 wt.%, with the balance being Mg and unavoidable impurities, wherein the total impurity content is ≤0.3 wt.%.

[0008] Preferably, the density of the magnesium-lithium alloy plate is less than 1.55 g / cm³. 3 The tensile strength is 158-181 MPa, the yield strength is 148-161 MPa, the elongation is 15-45%, and the cupping value is 8.5-13.0 mm.

[0009] This invention also provides a method for preparing an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation, specifically including the following steps: (1) Weigh out pure magnesium ingots, pure zinc ingots, magnesium-lithium master alloy, and magnesium-erbium master alloy as raw materials according to the mass percentage of the alloy plate composition; (2) Under an argon protective atmosphere, the raw materials from step (1) are heated and melted to prepare an alloy melt; (3) Cast the alloy melt obtained in step (2) into an alloy ingot; (4) After preheating the alloy ingot obtained in step (3), it is deformed by extrusion-online hot rolling composite process to obtain the target magnesium-lithium alloy plate.

[0010] Preferably, in step (2), the heating and melting temperature is 700-720℃.

[0011] Preferably, the specific operation of step (3) is as follows: after stirring and letting the alloy melt stand at 700-720℃, the waste residue is removed, the melt is poured into a stainless steel mold, cooled and shaped in a vacuum chamber, and then processed by wire cutting to obtain an alloy ingot.

[0012] Preferably, the specific operation of step (4) is as follows: after removing the surface oxide scale or contamination layer of the alloy ingot, it is placed in a heating furnace for preheating treatment, and then the preheated ingot is placed in an extruder for extrusion to obtain an extruded slab. Finally, the extruded slab is heated and rolled online to obtain a magnesium-lithium alloy rolled plate.

[0013] Preferably, the preheating temperature is 170-190℃ and the preheating time is 3-5 h; the extrusion forming conditions are: extrusion ratio 39:1, extrusion speed 1-2 m / min, and extrusion temperature 180℃; the heated rolling forming conditions are: rolling temperature 25-100℃ and total rolling reduction 65%-75%.

[0014] Therefore, the ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet and its preparation method based on Zn and Er grain boundary segregation provided by the present invention have the following beneficial effects: (1) By regulating the segregation of Zn and Er grain boundaries, the grain boundaries are effectively stabilized, the grains are refined, and the structure is homogenized, which significantly improves the deformation coordination of magnesium-lithium alloys and achieves high plasticity; (2) Homogenization of the microstructure can efficiently disperse deformation stress, inhibit crack initiation and propagation, and greatly improve forming performance, with a cupping value of more than 8.5 mm; (3) The alloy retains its ultra-lightweight properties and low density, while also possessing high plasticity and excellent formability, meeting the needs of lightweight fields such as electronic communications; (4) The preparation process is simple, requires no special equipment, is highly controllable, and has low cost, making it suitable for large-scale industrial production.

[0015] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0016] Figure 1 The images show the scanning electron microscope (SEM) microstructure of recrystallized grains in the magnesium-lithium alloy plate prepared in Example 1 of the present invention, wherein: (a) and (b) are images under different fields of view, and the "DRXed" label in the images indicates dynamically recrystallized grains, with a scale bar of 2 μm; Figure 2 The following are the results of transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS) elemental distribution analysis at the grain boundaries of recrystallized grains in the magnesium-lithium alloy plate prepared in Example 1 of this invention, wherein: (ac) is a BF-STEM image of the precipitated phase inside the grain; (d) is an EDS distribution map of Mg; (e) is an EDS distribution map of Zn; and (f) is an EDS distribution map of Er. Figure 3 The image shows the energy dispersive spectral analysis of Er element at the grain boundaries of recrystallized grains in the magnesium-lithium alloy plate prepared in Example 1 of this invention; where: (a) is the line scan region selected for the grain boundary; (b) is the line scan image corresponding to the green arrow; Figure 4 The figures show the room temperature tensile stress-strain curves of the magnesium-lithium alloy plates prepared in Examples 1-4 and Comparative Examples 1-2 of this invention. Figure 5 The cupping test force-displacement curves, post-test sample photographs, and corresponding cupping values ​​(Erichsen values) of the magnesium-lithium alloy plates prepared in Examples 1-4 and Comparative Example 2 of this invention are shown. Figure 6 The morphology and microstructure of Comparative Example 1 of the present invention are shown below; wherein: (a) is an optical micrograph; (b) is a SEM morphology image; and (c) is a fracture surface morphology image. Figure 7 The images show the fracture morphology of Embodiment 1 and Comparative Example 2 of the present invention; wherein: (a) Embodiment 1; (b) Comparative Example 2. Detailed Implementation

[0017] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention. Furthermore, it should be understood that after reading the contents of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims and are all within the protection scope of the present invention.

[0018] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The term "embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment, nor does it specifically limit its independence or connection with other embodiments. In principle, in this application, as long as there are no technical contradictions or conflicts, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.

[0019] Unless otherwise defined, the technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the use of related terms herein is merely for the purpose of describing particular embodiments and is not intended to limit this application.

[0020] When a quantity, concentration, or other value or parameter is described as a range, preferred range, or preferred upper and lower limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper or preferred values ​​with any lower or preferred values, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical range values ​​listed herein include the endpoints of the range and all integers and fractions within that range.

[0021] Unless otherwise stated, all percentages, parts, ratios, etc. in this document are by weight.

[0022] Unless otherwise specified, the materials, reagents, instruments, and equipment used in this invention are all materials, reagents, instruments, and equipment routinely used by those skilled in the art, and the testing standards all use national or international standards commonly used in the field, without further explanation.

[0023] The pure magnesium ingots, pure zinc ingots, magnesium-lithium master alloys, and magnesium-erbium master alloys used in the embodiments of this invention are commercially available products.

[0024] The stretching machine used in this embodiment of the invention is a UTM4104. The metallurgical microscope used in this embodiment of the invention is an OLYMPUS PMG3. The scanning electron microscope used in this embodiment of the invention is a FEI NOVA 400. The heat treatment vacuum drying oven used in this embodiment of the invention is model DZF-6050BZ; In the embodiments of the present invention, the purity of the magnesium ingot is ≥99.95% and the purity of the pure zinc ingot is ≥99.99%; In this embodiment of the invention, the magnesium-lithium master alloy and the magnesium-erbium master alloy are collectively referred to as magnesium master alloys, and lithium and erbium in the magnesium master alloys account for 10-20% of the total mass of the magnesium master alloys, respectively. In this embodiment of the invention, the vacuum furnace is evacuated to a vacuum level of 2.5 × 10⁻⁶. -1 Pa, then argon gas is added as a protective gas until the entire vacuum furnace is in a protective gas atmosphere for melting.

[0025] Example 1 This embodiment provides an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation, having the following composition by mass fraction: Li 10 wt.%, Zn 3 wt.%, Er 2.5 wt.%, with the remainder being magnesium and unavoidable impurities, the total impurity content being ≤0.3 wt.%.

[0026] The preparation method of the above-mentioned high-plasticity and high-formability magnesium-lithium alloy sheet includes two stages: vacuum melting and casting, and extrusion-online rolling composite process. The specific steps are as follows: (1) Select pure magnesium ingots, pure zinc ingots, magnesium-lithium master alloys, and magnesium-erbium master alloys as raw materials according to the mass percentage of the selected alloy components in the above high-plasticity and high-formability magnesium-lithium alloy thin plates.

[0027] (2) Under the protection of argon, the raw materials obtained in step (1) are placed in a crucible and heated in a melting furnace to 720°C until all materials are completely melted to obtain an alloy melt.

[0028] (3) The alloy melt obtained in step (2) is stirred at a temperature of 710 °C until all raw materials are mixed evenly. The slag on the surface of the alloy melt is removed, and after standing for 5 minutes, it is poured into a stainless steel mold with a diameter of Φ90 and a length of 300 mm. After natural cooling in a vacuum furnace, an alloy ingot with a diameter of Φ80 is obtained by wire cutting.

[0029] (4) After removing the oxide scale or contamination layer from the surface of the alloy ingot obtained in step (3), it is placed in a heating furnace for preheating at 180 ℃ for 4 h. Then, the preheated alloy ingot is extruded on an extrusion press with an extrusion temperature of 180 ℃, an extrusion ratio of 39:1, and an extrusion speed of 1 m / min. The resulting extruded slab is subjected to online rolling deformation treatment and rolled at 100 ℃ with a total rolling reduction of 70% to obtain a magnesium-lithium alloy rolled sheet with a thickness of 0.6 mm.

[0030] Example 2 This embodiment provides an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation and its preparation method. The only difference from Embodiment 1 is that the rolling temperature in step (4) of this embodiment is 25 ℃. The rest is the same as in Embodiment 1 and will not be repeated here.

[0031] Example 3 This embodiment provides an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation and its preparation method. The only difference from Embodiment 1 is that the alloy composition in this embodiment is Li 9.0%, Zn 3.0%, Er 2.0%, with the balance being Mg. All other aspects are the same as in Embodiment 1 and will not be repeated here.

[0032] Example 4 This embodiment provides an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation and its preparation method. The only difference from Embodiment 1 is that the alloy composition in this embodiment is Li 11.0%, Zn 3.0%, Er 2.5%, with the balance being Mg. All other aspects are the same as in Embodiment 1 and will not be repeated here.

[0033] Comparative Example 1 This comparative example has the same composition as Example 1, being a cast Mg-10Li-3Zn-2.5Er alloy, but it has not undergone the extrusion-online hot rolling composite process. Everything else is the same as in Example 1, and will not be repeated here.

[0034] Comparative Example 2 The composition of this comparative example is the same as that of Example 1, except that the rolling temperature in this example is 150 ℃. Everything else is the same as in Example 1 and will not be repeated here.

[0035] The microstructure of the magnesium-lithium alloy rolled sheets obtained by the extrusion-online rolling composite process in Examples 1-4 was observed. Since the microstructure morphology of the magnesium-lithium alloy sheets obtained in each example is basically the same, only the microstructure image results of Example 1 are provided here. Figures 1-3 As shown.

[0036] Depend on Figure 1 It is known that the alloy microstructure consists of a large number of dynamically recrystallized grains with an average size of 0.5~2 μm. This fine-grained structure provides high-density grain boundaries for subsequent elemental segregation and is also the microstructural basis for the alloy's high plasticity. Figure 2 It is known that a 50-150 nm Zn-rich phase is distributed at the grain boundaries. During hot deformation, Zn atoms selectively segregate at the recrystallization grain boundaries, generating a solute dragging effect and inhibiting grain growth. The Zn-rich phase at the grain boundaries exhibits a discontinuous distribution, which is beneficial for maintaining the deformation coordination of the grain boundaries. Figure 3 It can be seen that Er exhibits a significant peak at the β-Li grain boundary, confirming the selective segregation of Er at the grain boundary and forming a synergistic segregation effect with Zn. This synergistic segregation is more effective than that of a single element in stabilizing grain boundaries, further suppressing grain coarsening and improving thermal stability.

[0037] The properties of the magnesium-lithium alloy rolled sheets prepared by the extrusion-online rolling composite process in Examples 1-4 were tested, and the stress-strain curves of the alloys are shown below. Figure 4 The force-displacement curves, sample photographs, and corresponding Erichsen values ​​from the cupping test are as follows: Figure 5 .

[0038] Depend on Figure 4 and Figure 5 The alloy obtained in Example 1 has the following properties: yield strength of 151 MPa, tensile strength of 162 MPa, elongation of 42.1%, cupping value of 9.71 mm, and density of 1.526 g / cm³. The alloy obtained in Example 2 has the following properties: yield strength of 148 MPa, tensile strength of 168 MPa, elongation of 16.0%, cupping value of 8.78 mm, and density of 1.526 g / cm³. 3 The alloy obtained in Example 3 has the following properties: yield strength of 161 MPa, tensile strength of 181 MPa, elongation of 18.6%, cupping value of 12.73 mm, and density of 1.542 g / cm³. 3 The alloy obtained in Example 3 has the following properties: yield strength of 150 MPa, tensile strength of 158 MPa, elongation of 38.3%, cupping value of 10.89 mm, and density of 1.513 g / cm³. 3 .

[0039] The microstructure and performance of the magnesium-lithium alloy rolled sheets obtained in Comparative Example 1 or Comparative Example 2 were observed and tested. The microstructure characterization is as follows: Figure 6 and Figure 7 As shown, the performance test results are as follows: Figure 4 and Figure 5 As shown.

[0040] Depend on Figure 6and Figure 4 It can be seen that the alloy obtained in Comparative Example 1 has coarse grains (100~200 μm), with a continuous network of Mg3Zn3Er2 phases at the grain boundaries. Zn and Er elements are mainly dissolved in the matrix, failing to achieve a grain refinement effect. This as-cast alloy has a room temperature elongation of only 2.1%, and its fracture surface exhibits typical brittle cleavage fracture. Figure 7 , Figure 4 and Figure 5 It can be seen that the rolling temperature has a significant impact on the grain size. At this temperature, the dynamic recrystallization of the alloy is sufficient, the grains coarsen, and the dimple size in the fracture morphology diagram (b) is significantly larger than that in Example 1 in Figure (a). Even though elemental segregation exists, grain coarsening under high-temperature rolling is unavoidable, causing the cupping value of the alloy to decrease to 4.33 mm.

[0041] In summary, the specific composition range proposed in this invention, combined with the extrusion-online hot rolling composite process, can induce synergistic segregation of Zn and Er at grain boundaries, thereby obtaining a fine-grained structure. This allows magnesium-lithium alloys to achieve a synergistic improvement in high plasticity (elongation 15~45%) and excellent formability (cupping value 8.5~13 mm) while maintaining ultra-light weight. Furthermore, the process window has a decisive influence on the final performance.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. An ultralight, high-plasticity, high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation, characterized in that, The magnesium-lithium alloy plate is composed of the following components by mass percentage: Li 5.0-15.0 wt.%, Zn 1.0-4.0 wt.%, Er 0.5-5.0 wt.%, with the balance being Mg and unavoidable impurities, wherein the total impurity content is ≤0.3 wt.%.

2. The ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation according to claim 1, characterized in that, The magnesium-lithium alloy plate is composed of the following components by mass percentage: Li 8.0-12.0 wt.%, Zn 2.5-3.5 wt.%, Er 1.5-3.0 wt.%, with the balance being Mg and unavoidable impurities, wherein the total impurity content is ≤0.3 wt.%.

3. The ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation according to claim 1, characterized in that, The density of the magnesium-lithium alloy plate is less than 1.55 g / cm³. 3 The tensile strength is 158-181 MPa, the yield strength is 148-161 MPa, the elongation is 15-45%, and the cupping value is 8.5-13.0 mm.

4. A method for preparing an ultralight, high-plasticity, high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation as described in any one of claims 1-3, characterized in that, Specifically, the following steps are included: (1) Weigh out pure magnesium ingots, pure zinc ingots, magnesium-lithium master alloy, and magnesium-erbium master alloy as raw materials according to the mass percentage of the alloy plate composition; (2) Under an argon protective atmosphere, the raw materials from step (1) are heated and melted to prepare an alloy melt; (3) Cast the alloy melt obtained in step (2) into an alloy ingot; (4) After preheating the alloy ingot obtained in step (3), it is deformed by extrusion-online hot rolling composite process to obtain the target magnesium-lithium alloy plate.

5. The method for preparing an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation according to claim 4, characterized in that, In step (2), the heating and melting temperature is 700-720℃.

6. The method for preparing an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation according to claim 4, characterized in that, The specific operation of step (3) is as follows: after stirring and letting the alloy melt stand at 700-720℃, the waste residue is removed, the melt is poured into a stainless steel mold, cooled and shaped in a vacuum chamber, and then processed by wire cutting to obtain an alloy ingot.

7. The method for preparing an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation according to claim 4, characterized in that, The specific operation of step (4) is as follows: after removing the oxide scale or contamination layer from the surface of the alloy ingot, it is placed in a heating furnace for preheating treatment, and then the preheated ingot is placed in an extruder for extrusion to obtain an extruded slab. Finally, the extruded slab is heated and rolled online to obtain a magnesium-lithium alloy rolled plate.

8. The method for preparing an ultralight, high-plasticity, and high-formability magnesium-lithium alloy sheet based on Zn and Er grain boundary segregation according to claim 7, characterized in that, The preheating temperature is 170-190℃ and the preheating time is 3-5 h; the extrusion forming conditions are: extrusion ratio 39:1, extrusion speed 1-2 m / min, and extrusion temperature 180℃; the hot rolling forming conditions are: rolling temperature 25-100℃ and total rolling reduction 65%-75%.